Impacts of Two Types of El Niño and La Niña Events on Typhoon Activity - Po-Chun Hsu; Chung-Ru Ho; Shin-Jye Liang; Nan-Jung Kuo (Advances in Meteorology)
The HadISST (Hadley Centre Sea Ice and Sea Surface Temperature) dataset is used to define the years of El Niño, El Niño Modoki, and La Niña events and to find out the impacts of these events on typhoon activity. The results show that the formation positions of typhoon are farther eastward moving in El Niño years than in La Niña years and much further eastward in El Niño Modoki years. The lifetime and the distance of movement are longer, and the intensity of typhoons is stronger in El Niño and in El Niño Modoki years than in La Niña years. The Accumulated Cyclone Energy of typhoon is highly correlated with the Oceanic Niño Index with a correlation coefficient of 0.79. We also find that the typhoons anomalously decrease during El Niño years but increase during El Niño Modoki years. Besides, there are two types of El Niño Modoki, I and II. The intensity of typhoon in El Niño Modoki I years is stronger than in El Niño Modoki II years. Furthermore, the centroid position of the Western Pacific Warm Pool is strongly related to the area of typhoon formation with a correlation coefficient of 0.95.